炸制过程中油脂氧化对鱼饼中晚期糖基化 终末产物生成的影响Effect of oil oxidation on formation of advanced glycation end products in fish cakes during frying process - 胡本伦，武润琳，孙靖雯，贾才华，荣建华，刘茹 HU Benlun, WU Runlin, SUN Jingwen, JIA Caihua, RONG Jianhua, LIU Ru (Zhongguo youzhi, 2023)
旨在为炸制鱼饼中晚期糖基化终末产物（AGEs）含量的控制提供理论依据和参考，以冷冻鲢鱼糜为原料制作鱼饼，通过分析连续炸制过程中（每3 h炸制1次）鱼饼中AGEs的生成与其理化指标和油脂氧化程度之间的相关性，探讨炸制过程中油脂氧化对鱼饼中AGEs生成的影响。结果表明：鱼饼外层AGEs含量显著高于内层，炸制9~18 h，鱼饼AGEs含量显著高于其他阶段（p<0.05）；鱼饼中AGEs含量与水分含量呈极显著负相关，与脂肪含量和丙二醛含量呈极显著正相关，说明水分散失、油脂吸收以及油脂氧化促进了AGEs的生成。综上，在连续炸制过程的中期，鱼饼中水分含量较低，油脂氧化较为严重，AGEs含量较高。In order to provide theoretical basis and reference for the control of advanced glycation end products (AGEs) content in fried fish cakes, fish cakes were prepared from frozen silver carp surimi, and the correlation between physicochemical indexes and oil oxidation degree and the content of AGEs in fish cakes during continuous frying (once every 3 h) were analyzed to explore the effect of oil oxidation on the formation of AGEs. The results showed that the content of AGEs in the outside of fish cakes was significantly higher than that in the inside of fish cakes. The content of AGEs from 9 h to 18 h were significantly higher than that in others (p<0.05). The content of AGEs was significantly negatively correlated with the water content, and significantly positively correlated with oil content and MDA content, indicating that water volatilization, oil absorption and oxidation promoted the formation of AGEs. In summary, the AGEs content is relatively higher in the middle stage of the continuous frying process due to the relatively lower water content and serious oxidation of oil.